Awareness Regarding Occupational Hazards Among the Dental Students of a Medical College of Nepal - Adhikari, S; Bhattarai, R (Journal of Nepalese Prosthodontic Society, 2022)
Introduction: Dental students, during their clinical and preclinical practices, are constantly exposed to a number of occupational hazards. Such exposures lead to various ailments and diseases. The study was done to assess the awareness regarding occupational hazards among dental students in College of Medical Sciences, Nepal.Methods: A questionnaire-based, descriptive cross-sectional study was conducted among the dental students from College of Medical Sciences, Nepal. Demographic details and awareness on different variables like bioaerosols, X-rays, blue light radiation, vibration, noise, posture, ergonomics, mercury vapour inhalation and percutaneous incidents, were assessed with the close-ended questions.Questionnaire was delivered to the participants in paper-printed forms. Data analysis was done using SPSS version 17. Chi-square tests were done to find the association between the variables to education and gender and the level of significance was set at p